2008
DOI: 10.1007/s12011-007-8069-4
|View full text |Cite
|
Sign up to set email alerts
|

Rubisco Activase mRNA Expression in Spinach: Modulation by Nanoanatase Treatment

Abstract: Characterized by a photocatalysis property, nanoanatase is closely related to the photosynthesis of spinach. It could not only improve light absorbance, transformation from light energy to electron energy, and active chemical energy, but also promote carbon dioxide (CO(2)) assimilation of spinach. However, the molecular mechanism of carbon reaction promoted by nanoanatase remains largely unclear. In this study, we report that the amounts of Rubisco activase (rca) mRNA in the nanoanatase-treated spinach were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…From the follow-up studies, the authors reported enhanced activity of rubisco activase, rubisco carboxylation, rate of photosynthetic carbon reaction and chlorophyll content that could have resulted in increased plant dry weight [6,7]. From a later study in spinach, nano-TiO 2 treatment was found to improve light absorbance, transformation from light energy to electron energy and chemical energy, and promoted carbon dioxide assimilation [8]. Magnetic nanopartciles coated with tetramethylammonium hydroxide also led to an increase in chlorophyll-a level in maize [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the follow-up studies, the authors reported enhanced activity of rubisco activase, rubisco carboxylation, rate of photosynthetic carbon reaction and chlorophyll content that could have resulted in increased plant dry weight [6,7]. From a later study in spinach, nano-TiO 2 treatment was found to improve light absorbance, transformation from light energy to electron energy and chemical energy, and promoted carbon dioxide assimilation [8]. Magnetic nanopartciles coated with tetramethylammonium hydroxide also led to an increase in chlorophyll-a level in maize [35].…”
Section: Discussionmentioning
confidence: 99%
“…The positive morphological effects included enhanced germination percentage and rate; length of root and shoot, and their ratio; and vegetative biomass of seedlings in many crop plants including corn, wheat, ryegrass, alfalfa, soybean, rape, tomato, radish, lettuce, spinach, onion, pumpkin and cucumber. Enhancement of many physiological parameters related to plant growth and development were also reported that include enhanced photosynthetic activity and nitrogen metabolism by MBNMs in a few crops including soybean [3], spinach [4-8], and peanut [9] and by multiwalled carbon nanotubes (MWCNTs) in tomato [10]. Only recently, the genetic implications of such nanoparticle-induced positive changes have been validated through investigations on enhanced mRNA expression and protein level in spinach [6] by nano-TiO 2 , generational transmission of fullerol through seeds in rice [11], and changes in gene expression at plant and cellular level in tomato and tobacco [12,13] by MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Some research has indicated that exposure toTiO 2 MNMs may be beneficial to plants. A series of related studies were conducted exposing spinach (Spinacia oleracea) to 4-6 nm TiO 2 (anatase) MNMs at 0.25% (w/v) (Gao et al, 2006;Linglan et al, 2008;Yang et al, 2007). Exposure to TiO 2 MNMs increased biomass, photosynthesis rate, and enzyme activity.…”
Section: Tio 2 and Znomentioning
confidence: 99%
“…A higher concentration of NPs may cause structural damage to cells and interfere in vital metabolic processes. Lin and Xing observed that ZnO NPs applied to soil significantly reduced the biomass of ryegrass . The anatomical study of roots showed shrinkage of the root tip.…”
Section: Np Effects On Plant Growth and Mechanism Of Actionmentioning
confidence: 99%
“…NPs accumulated on the root hairs and surface of feeder roots; as a result, absorption of water and minerals was adversely affected. One study found that NPs reached the apoplast and protoplast in the endodermal and stelar cells of the root, but the particles were profusely stuck at the root surface . Rico et al cultivated three cultivars of rice with various amylose character (low, medium, and high) in the soil applied with 500 mg CeO 2 NPs per kg soil .…”
Section: Np Effects On Plant Growth and Mechanism Of Actionmentioning
confidence: 99%